ICT PERSONNEL MATURITY TOWARDS GREEN ICT IN KENYA (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Though ICT is contributing to the economy associated with innovations, inventions and rapid development in almost all aspects of human life, is responsible for climatic degradation. The rapid increase of ICT usage means more costs of doing business, energy consumption, and more environmental challenges. The rapid changing technology reaching Kenya and lack of their understanding has put a lot of pressure on both management and ICT personnel to implement them on a trial and error manner. This has limited the gains meant to be obtained from green ICT despite its technologies availability. The lack of ICT personnel capacity readiness challenges the reaping of green ICT benefits. The study was informed by the G-readiness model and the enhanced G-readiness model. This study purposed to determine the personnel capacities readiness towards green ICT in Kenya. The study was undertaken using the interpretive, inductive multi-case survey study on a population of four data centres and 116 ICT managerial, technical and user personnel that were purposively sampled. Interview, observation, questionnaire and document analysis methods were used to gather data that was triangulated to increase the reliability and validity. The study established the ICT personnel’s G-readiness was very low on both training and professional development perspectives in Kenya. The study’s findings are useful towards the strategic planning for green ICT implementation, cutting down running costs, improving environmental performance of organisations and contribution to the world of knowledge. The findings provide data for informed ICT personnel and workplace readiness alignment, decision making and ICT curriculum development. The study recommends application of green ICT based on established ICT personnel capacity, inclusion of green ICT training in the curriculum, creation of green ICT responsibilities, provision for a green ICT budget and investment into the development of green ICT personnel